Iron-Polyphenol Interaction Reduces Iron Bioavailability in Fortified Tea: Competing Complexation to Ensure Iron Bioavailability - V. Dueik; B. K. Chen; L. L. Diosady (Journal of Food Quality)
Tea seems to be like a logical substrate for iron fortification; however, its fortification with iron presents technical challenges as tea polyphenols form a blue complex with iron that makes both of them unavailable for absorption. The objective of this work was to develop an effective technology, to prevent the interaction of iron and polyphenols by using EDTA as a competing complexing agent. Fortified tea was prepared from premix, prepared by spraying iron and sodium EDTA into tea leaves. Iron concentration in tea was adjusted to 5 mg/cup. Iron content was measured by AAS and the iron-polyphenol complex by spectrophotometry at 560 nm. Sensory evaluation was carried out in order to determine if fortification affects the properties of tea. A molar ratio of 1 : 2 Fe : EDTA was able to avoid complex formation and provide 4 mg of iron per cup of brewed tea. The fortified tea had a similar colour and flavour as ordinary tea, without the development of off-flavours. However, fortified tea with a ratio lower than 1 : 2 had a darker colour and off-flavours. By the addition of EDTA in a molar ratio ≥1 : 2, it is possible to produce an iron fortified tea without the formation of off-flavours.